Prevalence and Clinical Characteristics of NEUROD1‐MODY in Chinese Early‐Onset Type 2 Diabetes Mellitus and a Literature Review - Tianhao Ba; Qian Ren; Siqian Gong; Meng Li; Hong Lian; Xiaoling Cai; Wei Liu; Yingying Luo; Simin Zhang; Rui Zhang; Lingli Zhou; Yu Zhu; et al. (Journal of Diabetes)
ABSTRACT Background Maturity‐onset diabetes of the young resulting from mutations of the NEUROD1 gene (NEUROD1‐MODY) is a rare form of diabetes and has not been well studied. We aimed to estimate its prevalence in Chinese patients with early‐onset type 2 diabetes mellitus (EOD) and summarize its clinical and genetic characteristics. Methods We performed next‐generation sequencing in 679 patients with EOD to screen rare variants in NEUROD1 exons and evaluated the effects of variants using in vitro experiments. All the reported NEUROD1‐MODY cases were reviewed. Patients carrying pathogenic or likely pathogenic variants were diagnosed with NEUROD1‐MODY according to the American College of Medical Genetics and Genomics guidelines. Results Four rare variants were identified in 679 patients with EOD, but only P197H decreased the transcriptional activity in in vitro functional assays to an extent comparable to the well‐known mutation causing NEUROD1‐MODY. Its frequency was pretty higher in the European population (0.024) than that in the East Asian population (0.00034) according to the gnomAD database. Twenty‐eight previously reported patients could be confirmed as diagnosed. The patients in Asia had a lower body mass index and a higher rate of ketosis compared with Caucasians, and the mutations present in Asia often occurred in the transactivation domain. Neurological abnormalities were observed in 10.7% of the patients with NEUROD1‐MODY. Conclusions NEUROD1‐MODY in Chinese patients with EOD is not common (≤ 0.15%). The P197H might account for MODY in Chinese with a higher penetrance than Caucasian and needs further exploration. The possible differences of phenotypes exist between the two ethnic populations.